Risk factors associated with violence against elderly in a family setting - Risović Katarina; Rusac Silvia; Todorović Nataša (Temida, 2018)
Violence as a social phenomenon does not know the age of a victim. It is happening at all stages of life and among members of all age groups. Ageing of the population and an increasing emphasis on its problems, among other things, raises the issue of violence against the elderly which is happening in their homes. Incorrect assumptions that violence occurs in institutions rather than in the family contributes to ignoring the problem. A combination of individual, relational, community, and societal factors contribute to the risk of becoming a victim and a perpetrator of elder abuse. Based on the so far research and knowledge, the paper aims to point out to the risk factor for elder abuse in order to sensitize and foster public and scientific community on activism, discovering and solving problems related to elder abuse in the family setting.